Kajian Estetika Melalui Bentuk Keseimbangan Ilustrasi Durga Dengan Teknik Sablon Discharge Sederhana - Novitasari, Dwi (LPPM STMIK STIKOM Indonesia, 2018)
This study purpose is to analyze esthetic characters on Durga illustration with simple discharge screen printing technique. As many people know, Durga visualization is more identically spooky impression. Durga illustration used as reference or as an object on simple discharge screen printing technique, which is a type of screen print that removes the basic color of the fabric with chlorine material as a mixture of ink, produce a distinctive color effect and different from the usual screen printing techniques. This study will focus on the form balance and aesthetic characteristics or properties such as complexity, it becomes interesting to study. Furthermore in this writing using qualitative descriptive method in order to get a systematic, factual, and accurate overview of aesthetics through the balance form of Durga illustration with a simple discharge screening technique.